StyleGAN2-ADA and Real-ESRGAN: Thai font generation with generative adversarial networks - Nitisukanan, Nidchapan; Boonthaweechok, Chotika; Tiawpanichkij, Prapatsorn; Pissakul, Juthamas; Maneesawangwong, Naliya; Siriborvornratanakul, Thitirat (Advances in computational intelligence, 2024)
Contemporary font design is a labor-intensive process. To address this, we utilize deep learning, specifically StyleGAN2-ADA and Real-ESRGAN, for automated Thai font generation. StyleGAN2-ADA incorporates adaptive discriminator augmentation (ADA) for image synthesis. By integrating Real-ESRGAN, font quality is enhanced. Our approach produces diverse, high-resolution fonts, as demonstrated in comparative experiments. In a survey with 50 participants, StyleGAN2-ADA without augmentation proves superior in legibility and visual appeal, while StyleGAN2-ADA with augmentation excels in diversity. This research highlights the efficiency of deep learning in creating high-quality Thai fonts and has implications for automated font design advancement.